The qur’anic contributions to the growth of yoruba semantics (2006)
The Qur’an is a literal transcript of the word o f God form a safety preserved tablet in between revealed to Muhammad far the period of 23 years in Arabic; the Qur’an, an ’eye opener’ an illuminating light and original source of branches of the knowledge. It is really in existence to withstand the test of time. This paper aims at examining the impact of the Qur’an on the growth of Yoruba semantics. It firstly treats how the Qur’an was the compendium of branches of knowledge, its characteristic feature, its influence on the language in which it was revealed - Arabic - then on other languages. Such influence cuts across philosophical aspects of the language. It is the accurate and powerful descriptive language of the Qur’an that has led many researchers of different fields to have discovered new inventories described about fifteen hundred years ago with modem equipment. The historical account of Yoruba contact with the Qur’an vis-à-vis Islam throws light on the period when the Yoruba had felt the impact of the Qur’an on their language. Semantics and its refetents will be dealt with in application o f the meaning of Quranic verses that contribution to the growth of Yoruba semantics. This focus would be the main study in which each word examined will be instanced with the Quranic verse. This study will also reveal that not only in Arabic language that the Qur’an is believed to represent the highest linguistic and semantic achievement but also in Yoruba language if it is critically studied.